Crisphead lettuce (lactuca sativa l.) cultivar evaluation and response of transplants to nitrogen nutrition - Botha, Christelle Charle (University of Pretoria, 2013)
Dissertation (M Inst Agrar (Horticulture))--University of Pretoria, 2007.